Vpliv skupkov nehomogenosti zaradi tlačnega litja na dobo trajanja ulitkov - Tomažinčič, Dejan (visokošolska dela, 2021)
When dealing with casted parts most research to this date is limited to the influence of individual and isolated pores. This doctoral dissertation therefore focuses on the less researched area of the influence of large-scale macro porosity on fatigue life. It is a comprehensive study of commonly used aluminium alloy in the foundry industry AlSi9Cu3. An important segment of research is a description of the identified macroporous defects, i.e. pores and cold shuts with the voxel technique, which is then compared with the alternative technique of defect description using a vector segmentation technique. By applying a reversed engineering the porosity is modelled on the basis of (mi)-CT scans and then used for the numerical calculation of the fatigue life according to the theory of lowcyclic fatigue with the commercial SIMULIA software (Abaqus and fe-safe). The study serves as an aid in assessing when castings parts may still be useful and when the risks of rapid initiation of fatigue damage due to the pore clusters present are too great. Through analyses, different metallurgical defects can be compared and estimated which defects have greater and which less effect on the reduction of fatigue life. Experimental-theoretical comparisons of the durability of different cellular structures with a negative Poisson ratio from the Al7075-T651 alloy are also included in the research with an objective to first test the proposed methodology on the cases of regular geometric inhomogeneities. The overall results indicate the acquisition of useful new tools that can be used to assess both the ordered and random porous structures, in order to assess whether these still allow functional operation and the required fatigue life of the product.
Keywords: aluminijeva zlitina; aluminium alloy; auxetics; avksetičnost; damage; Disertacije; disipacija energije; dissertations; energy dissipation; finite element method; high-pressure die casting; low-cycle fatigue; macroporosity; makro poroznost; malociklična trdnost; metoda končnih elementov; poškodbe; povratni inženiring; reverse engineering; Taguchi method; Taguchijeva metoda; Tlačno litje; visokotlačno litje